Liderazgo directivo cultura organizacional y desempeño educativo de los docentes en las instituciones educativas de la provincia de Requena 2022 - Ampuero Gonzalez, Anny Maribel (2024)
The present research had the following main question: To what extent do managerial leadership and organizational culture influence the educational performance of teachers in Educational Institutions in the province of Requena, 2021? And as a general objective: To explain the influence of managerial leadership and organizational culture on the educational performance of teachers in the Educational Institutions of the province of Requena, 2021. The study is explanatory, because it is not only made up of descriptions, but also explains in detail the influence of managerial leadership and organizational culture on the educational performance of teachers. The design is field-based, cross-sectional and multivariate. It was made up of 41 directors and 26 deputy directors, making a total of 67 respondents. The technique used for data collection was the survey, and the instrument was the questionnaire. The study concludes that, "There is a significant influence of managerial leadership and organizational culture on the educational performance of teachers in the Educational Institutions of the province of Requena, 2021. In other words, the coefficient of managerial leadership (β1 = 2.204) is the ratio of change in educational performance for each unit of educational leadership (p-value = 0.017<0,05). On the other hand, β2 = 2.932, the rate of change in educational performance for each unit of the organizational culture (p-value = 0.003<0.05).